The effects of caffeine mouth rinsing on exercise performance: a systematic review - Ehlert, A. M.; Twiddy, H. M.; Wilson, P. B. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
Caffeine ingestion can improve performance across a variety of exercise modalities but can also elicit negative side effects in some individuals. Thus, there is a growing interest in the use of caffeine mouth rinse solutions to improve sport and exercise performance while minimizing caffeine`s potentially adverse effects. Mouth rinse protocols involve swilling a solution within the oral cavity for a short time (e.g., 5-10 s) before expectorating it to avoid systemic absorption. This is believed to improve performance via activation of taste receptors and stimulation of the central nervous system. Although reviews of the literature indicate that carbohydrate mouth rinsing can improve exercise performance in some situations, there has been no attempt to systematically review the available literature on caffeine mouth rinsing and its effects on exercise performance. To fill this gap, a systematic literature search of three databases (PubMed, SPORTDiscus, and Web of Science) was conducted by two independent reviewers. The search resulted in 11 randomized crossover studies that were appraised and reviewed. Three studies found significant positive effects of caffeine mouth rinsing on exercise performance, whereas the remaining eight found no improvements or only suggestive benefits. The mixed results may be due to heterogeneity in the methods across studies, interindividual differences in bitter tasting, and differences in the concentrations of caffeine solutions. Future studies should evaluate how manipulating the concentration of caffeine solutions, habitual caffeine intake, and genetic modifiers of bitter taste influence the efficacy of caffeine mouth rinsing as an ergogenic strategy.